(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
The performance of the single-stage and double-stage two-bladed micro-sized turbines for the Rain Water Harvesting (RWH) System is investigated in this article. The RWH system is a technique of collecting rainwater and storing it in a tank before reusing it for a specific purpose. The emphasis of this paper’s performance analysis was on the electrical generating capacity of the Savonius turbine. The Savonius turbines were developed and constructed out of an aluminum sheet with an aspect ratio of 1.8, a height of 8 cm, and a diameter of 4.5 cm. When incoming water travels from the water tank via the micro-Savonius blades in the pipeline, the performance of single-stage and double stage designs is evaluated in terms of electrical power production. According to the findings, the planned and constructed systems work well in terms of maintaining a constant voltage and current. The single-stage rotor outperformed the two-stage rotor, which can create almost twice the power. When a single-stage two-bladed Savonius rotor is utilized instead of a double-stage rotor, the rotor may spin at up to 1280 rpm. The two-bladed Savonius micro-turbine has a single stage and can light 0.3 watt LED lights.